"To be songe to the tune of [the] 25th psalme": Adapting The Whole Booke of Psalmes for Personal Devotion and Communal Singing. Issue 1 (2nd January 2022) - Arten, Samantha
ABSTRACT: By the end of the sixteenth century, The Whole Booke of Psalmes (1562, with yearly reprints) had become a symbol of English Protestantism, and its monophonic metrical psalms a hallmark of English Protestant music. Yet the psalter's success, illustrated by its rapid and enthusiastic adoption by the English people for public worship and private devotion, was due in part to audiences failing to use it as directed. Close study of 133 editions, 222 book-copies, shows that in their use of the book, many readers of the WBP freely adapted this psalter to navigate a myriad of problems related to its printing—memorization demanded by page turns, conflicting tune references, and music typesetting errors—and to accommodate their own religious and musical desires. Congregations and individuals interacted with their WBP s in a dynamic process, freely adapting its texts, music, and even the pages themselves for purposes of convenience, recreation, and devotion.